2010
DOI: 10.1167/10.6.19
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic perception of real depths at large distances

Abstract: There has been no direct examination of stereoscopic depth perception at very large observation distances and depths. We measured perceptions of depth magnitude at distances where it is frequently reported without evidence that stereopsis is non-functional. We adapted methods pioneered at distances up to 9 m by R. S. Allison, B. J. Gillam, and E. Vecellio (2009) for use in a 381-m-long railway tunnel. Pairs of Light Emitting Diode (LED) targets were presented either in complete darkness or with the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 33 publications
1
61
0
Order By: Relevance
“…Beyond a hundred meters, even very large absolute depth separations produce uncrossed disparities that are very small (Ogle, 1950;Palmisano et al, 2010). Ogle suggested that stereopsis should no longer be apparent beyond 300-650m where the size of binocular disparities is below detection thresholds (Ogle, 1950).…”
Section: Stereopsis In Real Scenes and The Magnitude Of Binocular Dismentioning
confidence: 99%
“…Beyond a hundred meters, even very large absolute depth separations produce uncrossed disparities that are very small (Ogle, 1950;Palmisano et al, 2010). Ogle suggested that stereopsis should no longer be apparent beyond 300-650m where the size of binocular disparities is below detection thresholds (Ogle, 1950).…”
Section: Stereopsis In Real Scenes and The Magnitude Of Binocular Dismentioning
confidence: 99%
“…Stereoacuity is naturally limited with a conservative threshold of about 10 seconds of arc [20]. Considering this threshold and referring to Equation 1, the maximum distance at which stereopsis may produce usable data would be ca.…”
Section: Stereopsismentioning
confidence: 99%
“…While research has provided evidence that binocular disparity can enable improved distance perception for distances as far as 40 meters away [38], the usefulness of stereo for practical spatial tasks is generally limited to 10 meters, and is best within one meter [39]. It follows, then, that stereo would be most helpful for close-range spatial inspection tasks (which our task was, as participants moved up close to potential collision areas in order to make judgments).…”
Section: Perceptual Cues and Spatial Tasksmentioning
confidence: 99%